Enhancing Akidah and Akhlak Understanding Through Problem-Based Learning Model at MIS Hizbul Wathan NW - Harum; Bahrudin (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This Classroom Action Research (CAR) aims to explore the effectiveness of the Problem-Based Learning (PBL) model in enhancing students’ understanding of Akidah and Akhlak at MIS Hizbul Wathan NW. Akidah and Akhlak, being core subjects in Islamic education, require a teaching approach that not only provides theoretical knowledge but also encourages students to internalize and apply ethical and religious principles in their daily lives. The PBL model, which emphasizes real-world problem-solving and critical thinking, is believed to be an effective method to foster deeper understanding and engagement in these subjects. This research was conducted in two cycles, each involving stages of planning, implementation, observation, and reflection. Data was collected through classroom observations, student assessments, and interviews with both teachers and students. The findings reveal that the PBL model significantly improves students’ ability to relate Akidah and Akhlak teachings to real-life situations. By engaging with problems that require critical thinking and decision-making, students develop a deeper understanding of Islamic beliefs and moral values. Furthermore, the collaborative nature of PBL enhances students’ communication skills and teamwork, which are crucial for their personal and social development. This study concludes that Problem-Based Learning is an effective pedagogical model for teaching Akidah and Akhlak, as it promotes active learning, critical thinking, and the application of Islamic teachings in everyday life. The results of this research offer valuable insights for educators looking to implement more interactive and student-centered approaches in Islamic education.